Effect of dietary Moringa stem meal level on growth performance, slaughter performance and serum biochemical parameters in geese. Issue 1 (18th September 2019) - Zhai, Shuangshuang; Li, Miaomiao; Li, Mengmeng; Zhang, Xiufen; Ye, Hui; Lin, Zhenping; Wang, Wence; Zhu, Yongwen; Yang, Lin
Abstract: Moringa stem meal (MSM) with a high level of crude fibre (CF) might be developed and utilized in herbivorous geese as an unconventional feedstuff. The aim of this study was to investigate the effect of the MSM level in the diet on the growth performance, slaughter performance, breast meat quality and serum biochemical parameters in geese from 22 to 70 days of age. A one‐factor completely randomized design was adopted in our study. A total of one thousand eight 21‐day‐old geese were randomly divided into six groups, with six replicates per group and 28 birds per replicate. The geese were fed diets containing MSM levels of 0, 20, 40, 60, 80 or 100 g/kg during day 22–70. The dietary MSM level had no effect ( p > .05) on the final body weight (BW), average daily gain (ADG) or average daily feed intake (ADFI). The feed/gain ratio (F/G) increased linearly ( p < .001) as the dietary MSM level increased. No differences ( p > .05) were observed in the slaughter performance, meat quality and the relative organ weight (except for thymus) of the geese ( p > .05). The relative weight of the thymus in the geese fed diets with supplementation of MSM was higher than that in the non‐supplemented MSM control group ( p < .05). In addition, 100 g MSM/kg of diet decreased the serum glucose (GLU) level ( p < .05) and increased the alanine transaminase (ALT) enzyme activity ( p = .03). Dietary MSM levels of no more than 60 g/kg had no effects on the growth performance and slaughter performance, whereas diets with 100 g MSM/kg increased the F/G and serum ALT enzyme activity, as well as decreasing the serum GLU level. Therefore, MSM provided at a reasonable level could be developed as an unconventional feedstuff for geese at the finisher period.